Robust Fuzzy MIMO Bang-Bang Controller for two links robot manipulators - Marwan A.; Nagi F.; Sahari K.S.M.; Hanim S. (2023)
In this paper a new fuzzy controller for multi-input-multi-output (MIMO) systems has been proposed. The new MIMO self-tuning robust controller is called as Fuzzy Bang-Bang Controller (FBBC) and is used for rigid-type robot which has two links manipulators. The controller operation is demonstrated by simulation of manipulators movement from any initial position to up and downward positions. The comparison between the proposed controller and Slide Mode Controller (SMC) is carried out for to tracking performance ability. The comparison is based on: the speed of convergences, maximum payload, amplitude and frequency. It was concluded that based on the tables and the simulation results proposed controller is better than slide mode controller (SMC) in handle big load, amplitude and frequency.